Analisa Kualitas Aplikasi Performance Simanis dengan Metode End User Computing Satisfaction (EUCS) - Meidita Nurul Farisi; Eva Zuraidah (Journal of Informatics Management and Information Technology, 2022)
A process to find and find out the extent of an information system implementation activity from the point of view of an information system evaluation. It aims to determine the level of user satisfaction in using a system. This study was conducted to measure the quality of the Simanis application using the End User Computing Satisfaction (EUCS) method, as well as using questionnaires to respondents and IPA Importance Performance Analysis. The results of the application quality level still need to be evaluated because the GAP level of 5 dimensions, namely content (content), accuracy (accuracy), appearance (format), user satisfaction (easy to use), and timeliness (timeliness) is still far from user expectations. The results of the user assessment of the Simanis performance application, no attributes found in quadrant 1. This indicates that the priority level for changes in some features does not exist, meaning that the features already provide the needs of the users. Suggestions in this study, application developers must continue to meet the performance expectations of the Simanis application in the 5 dimensions that have been assessed.